The Diffusion of New Age Practices and Beliefs among Australian Church Attenders - Possamai, Adam; Bellamy, John; Castle, Keith (Fieldwork in Religion, 2007)
Analysing the results of a 2001 survey of a random sample of churchgoers in Australia, this article discovers that if all churchgoers are analysed as one single category, Australian churchgoers do not have much affinity with the New Age, a result which fits with the current literature. However, when looking more closely at the sample, it is discovered that Catholics do have the highest affinity with the New Age among all Christian groups, and evangelical groups have the least affinity. It is also found that churchgoers in their teens are more inclined to these alternative ideas.